2023
DOI: 10.3390/geriatrics8020044
|View full text |Cite
|
Sign up to set email alerts
|

Early Feasibility of an Activity-Based Intervention for Improving Ingestive Functions in Older Adults with Oropharyngeal Dysphagia

Abstract: There is growing awareness about the use of combined strength- and skill-based swallowing training for improving swallowing physiology in the event of dysphagia. Such an approach involves focusing on coordination and timing as well as swallowing strengthening in the context of increased exercise complexity in eating and drinking activities. This study aimed to determine the early feasibility of a newly developed 12-week intervention, named the ACT-ING program (ACTivity-based strength and skill training of swal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Rehabilitation studies into sarcopenic dysphagia in HNC are embryonic but have demonstrated encouraging results. A recent feasibility trial assessing the benefits of a strength and skill-based dysphagia rehabilitation programme included two participants with HNC who reported positive change [ 92 ]. A case study completed by Hashida et al [ 93 ] demonstrated improvements in sarcopenic dysphagia post-glossectomy following physical therapy, nutritional intervention and dysphagia therapy.…”
Section: Developing Areasmentioning
confidence: 99%
“…Rehabilitation studies into sarcopenic dysphagia in HNC are embryonic but have demonstrated encouraging results. A recent feasibility trial assessing the benefits of a strength and skill-based dysphagia rehabilitation programme included two participants with HNC who reported positive change [ 92 ]. A case study completed by Hashida et al [ 93 ] demonstrated improvements in sarcopenic dysphagia post-glossectomy following physical therapy, nutritional intervention and dysphagia therapy.…”
Section: Developing Areasmentioning
confidence: 99%
“…Interventional strategies for dysphagia are frequently employed in patients with Parkinson’s disease, stroke, multiple sclerosis, and oral cancer [ 8 , 14 ]. However, most previous research studies have focused on evaluating the effectiveness of these strategies specifically in stroke patients, with relatively few focusing on hospitalized older adult patients with swallowing difficulties.…”
Section: Introductionsmentioning
confidence: 99%